Testing of formed joints on a designed prototype station - Wróbel, Nikodem; Franka, Mateusz; Rejek, Michał; Li, Zhixiong; Królczyk, Jolanta; Śliwiński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
In presented paper perform prototype machine which consist of two independent motion axis equipped with force sensors. Used force sensors provide control of forming connection. Special design of the machine provide to make tensile strength test on it. Prepared nine samples to carried out tests, which revealed the influence between change of jaws displacement during plastic deformation and strength of that joint.
Keywords: formed joints; prototype stand; electric drives; clinching; designing of device and tooling